Role of heterotrimeric G proteins in platelet activation and clot formation in platelets treated with integrin αIIbβ3 inhibitor. (3rd April 2018) - Budnik, Ivan; Shenkman, Boris; Hauschner, Hagit; Zilinsky, Isaac; Savion, Naphtali
Abstract: Mechanisms of platelet activation are triggered by thrombin, adenosine diphosphate (ADP), epinephrine, thromboxane A2, and other soluble agonists which induce signaling via heterotrimeric Gαq, Gαi, and Gα12/13 proteins. We have undertaken a study addressing the contribution of these G proteins to platelet activation and clot formation in the presence of eptifibatide, thus excluding outside-in signaling provided by integrin αIIbβ3–fibrinogen engagement. Selective and combined activation of the G proteins was achieved by using combinations of platelet agonists and inhibitors. Platelet activation in platelet-rich plasma was evaluated by P-selectin expression using flow cytometry. Contribution of platelets to whole blood clotting was assessed by rotation thromboelastometry (ROTEM). Selective signaling of Gαq or Gαi but not Gα12/13 promoted P-selectin expression. Further enhancement of P-selectin expression was achieved by ADP-induced combined signaling of Gαq and Gαi, and to more extent by U46619 at high concentration (1.5 μM) induced combined signaling of Gαq and Gα12/13 while maximal P-selectin expression was achieved by thrombin receptor-activating peptide (TRAP)-induced combined signaling of Gαq, Gαi, and Gα12/13. In ROTEM, selective activation of Gαq, Gαi, or Gα12/13 failed to affect blood clotting. Combined signaling of Gαq and Gαi or Gαq and Gα12/13 or all three G proteins shortened the clotting time and stimulated clot strength. Pretreatment of platelets with acetylsalicylic acid did not change the effect of ADP but inhibited the effect of TRAP. Signaling of Gαq and Gα12/13 triggered by U46619 also stimulated clot formation. Combined signaling of either Gαq and Gαi or Gαq and Gα12/13 is sufficient to stimulate maximal platelet activation and enhanced clot formation in platelets treated with inhibitor of integrin αIIbβ3. It could be suggested that outside-in signaling is not necessarily required to fulfill these platelet functions.